2015
DOI: 10.1159/000369673
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for the Calcium Sensing Receptor in Rat Diabetic Encephalopathy

Abstract: Background: Diabetic encephalopathy is a common complication of diabetes, and it may be involved in altering intracellular calcium concentrations ([Ca2+]i) at its onset. The calcium sensing receptor (CaSR) is a G-protein coupled receptor, however, the functional involvement of CaSR in diabetic encephalopathy remains unclear. Methods: In this study, diabetic rats were modeled by STZ (50 mg/kg). At the end of 4, 8 and 12 weeks, the CaSR expression in hippocampus was analyzed by Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Indeed, previous studies have demonstrated that diabetic encephalopathy is one of the main complications of severe diabetes, and is believed to result from hyperglycemic and inflammatory damages to brain vessels and causes dementia [9][10][11][12]. Moreover, diabetes may increase the risk of developing mild cognitive impairment, a condition in which people experience more cognitive and memory problems than are usually present in normal aging [9][10][11][12]. Mild cognitive impairment may lead to Alzheimer's disease and other types of dementia [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, previous studies have demonstrated that diabetic encephalopathy is one of the main complications of severe diabetes, and is believed to result from hyperglycemic and inflammatory damages to brain vessels and causes dementia [9][10][11][12]. Moreover, diabetes may increase the risk of developing mild cognitive impairment, a condition in which people experience more cognitive and memory problems than are usually present in normal aging [9][10][11][12]. Mild cognitive impairment may lead to Alzheimer's disease and other types of dementia [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicate that diabetic patients are at higher risk of developing dementia or Alzheimer's disease [1][2][3][4][5]. Indeed, diabetes can cause several complications, including diabetic encephalopathy, which is believed to result from hyperglycemic and inflammatory damages to brain vessels and causes dementia [9][10][11][12]. The link between diabetes and Alzheimer's may occur as a result of the complex ways.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations